Psychic Numbing Al-Qur’an For Interpretation of verses of morality - Saiul Anah; Isa, Abdullah (Jurnal Keislaman, 2026)
The Qur'an emphasizes the importance of mental health in human life and the need for peace of mind, determination, and emotional balance in facing life's challenges the behavior or attitude of "Psychic Numbing Perspective of the Qur'an". How to find a solution can also be enlightening, so that the caring attitude between people can be applied, whether it is related to ethics or morals. And also always not to put forward the feelings of something, so that it doesn't influence oneself or even the environment, even more than that, it can be in accordance with the values of the Koran. Because since recently, life's problems are related to the need for solidarity or empathy, due to social, cultural and other inequalities. This type of research uses library research (library research). Qualitative research forms and data collection techniques with methods of analysis of primary data namely : (Al-Insyirah [94]: 1-8) These verses are samples to be used as authors to carry out analysis and solutions in dealing with the lack of or not caring, namely ego (psychic numbing) in the Qur'an. The results of this research show that the character or behavior of caring between people is a choice and a way of life in society. The attitude of empathy, isolidarity, that must always be started from personal self, from family to the level of society and to the highest institution. In implementing as well as finding solutions from the ipsychic nature of inumbing with in the self of every human being (human being), there are several things that must be paid attention to how the Al-Quran's solution must be made as a guide for life especially for every individual, family, or community by making it the "Value of the Imam" as a standard measure care, this is watch over to avoid indifferent behavior, imbecile, ignorant, not caring (don't care) or lack of isolidarity. The implication is that every family, social and social community must feel more and more responsible and strengthen their respective functions and roles as institutions for preaching the Qur'an, so that with them Islamic civilization will be more advanced with togetherness and intertwined concerns.